Rainfall Variability and Labor Allocation in Uzbekistan: The Role of Women's Empowerment - Vladimir Otrachshenko; Olga Popova; Nargiza Alimukhamedova (Institute of Labor Economics (IZA), 2023)
Employing novel household survey data, this paper examines how rainfall variability and mean temperature affect individual labor supply in Uzbekistan, a highly traditional lower-middle-income country in Central Asia. The findings suggest that rainfall variability induces the reallocation of labor supply: (i) out of agriculture to unemployment, (ii) from unemployment to business activities and irregular remunerated activities, and (iii) from being out of labor force to unemployment. These effects differ in rural and urban areas and by gender. In addition, active women's involvement in the labor market and household decision-making mediates the impact of climate variability on employment choices, especially in rural areas. This implies that traditional gender roles may make households in developing countries more vulnerable to adverse consequences of climate change, while women's empowerment may smooth such consequences.
Keywords: J16; J21; J43; P28; Q54; 330; rainfall variability; labor market; agriculture; employment; women's empowerment; Uzbekistan; Central Asia